2015
DOI: 10.1080/10408398.2013.779568
|View full text |Cite
|
Sign up to set email alerts
|

Extrusion and Extruded Products: Changes in Quality Attributes as Affected by Extrusion Process Parameters: A Review

Abstract: Extrusion of foods is an emerging technology for the food industries to process and market a large number of products of varying size, shape, texture, and taste. Extrusion cooking technology has led to production of wide variety of products like pasta, breakfast cereals, bread crumbs, biscuits, crackers, croutons, baby foods, snack foods, confectionery items, chewing gum, texturized vegetable protein (TVP), modified starch, pet foods, dried soups, dry beverage mixes etc. The functional properties of extruded f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
195
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 339 publications
(217 citation statements)
references
References 282 publications
12
195
0
10
Order By: Relevance
“…In conventional food extrusion, the material is moistened, heated under pressure, and mechanically sheared as it is conveyed. Extrusion is used in the production of breakfast cereals, some biscuits (Alam, Kaur, Khaira, & Gupta, 2016;Delcour et al, 2012;Hager, Zannini, & Arendt, 2012), and some meat analogues, but also in nonfood applications, such as the production of bioplastics. In extrusion, the formulation is generally subjected to elevated temperature, pressure, and shear.…”
Section: Development Of Reduced-gluten Wheat Products Using Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…In conventional food extrusion, the material is moistened, heated under pressure, and mechanically sheared as it is conveyed. Extrusion is used in the production of breakfast cereals, some biscuits (Alam, Kaur, Khaira, & Gupta, 2016;Delcour et al, 2012;Hager, Zannini, & Arendt, 2012), and some meat analogues, but also in nonfood applications, such as the production of bioplastics. In extrusion, the formulation is generally subjected to elevated temperature, pressure, and shear.…”
Section: Development Of Reduced-gluten Wheat Products Using Processingmentioning
confidence: 99%
“…Shomer, Lookhart, Salomon, Vasiliver, and Bean (1995) reported that albumins and globulins are more heat stable than HMW glutenins, while reported that γ -and α-gliadins are more heat labile than ω-gliadins. Protein polymerization is dominated by SS bond formation and mainly takes place in the extruder itself (Alam et al, 2016;Fischer, 2004;Pietsch, Emin, & Schuchmann, 2017). For meat analogues, the polymerization of wheat gluten largely determines end product quality (Pietsch, Emin, & Schuchmann, 2017).…”
Section: Development Of Reduced-gluten Wheat Products Using Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Food ingredients and their components undergo several transformations during extrusion cooking giving rise to extrudates with improved functionalities. The changes in the functional properties are related to the nutritional properties of extrudates …”
Section: Introductionmentioning
confidence: 99%
“…Extrusion is a modern processing method that can be used to process insects and insects-based products such as fish feeds. It has the benefits of improving the nutritional value of end products, destroying undesirable enzymes and anti-nutritional factors (Nikmaram et al 2015;Alam et al 2016;Filipovic et al 2010) and it has also been shown to enhance the apparent absorption of minerals (Razzaq et al 2012;Alonso et al 2001).…”
Section: Introductionmentioning
confidence: 99%